2011
DOI: 10.3109/09537104.2011.633646
|View full text |Cite
|
Sign up to set email alerts
|

CD72 gene expression in immune thrombocytopenia

Abstract: To explore the role of CD72 in the pathogenesis of immune thrombocytopenia (ITP), we detected CD72, Sema4D, IL-2, IL-4, and IFN-γ mRNA expressions and the levels of plasma Sema4D, IL-2, IL-4, IL-6, and IFN-γ in ITP patients (n = 39) and controls (n = 23). The levels of plasma IL-2, IL-4, and IL-6 were assayed by radioimmunoassay, and the levels of plasma IFN-γ and Sema4D were analyzed by enzyme-linked immunosorbent assay. Sema4D, CD72, IL-2, IFN-γ, and IL-4mRNA expressions were analyzed by real-time quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…CD27 − B cells showed normal or slightly increased expression of CD72. Despite the fact that CD100 expression was reported not to be increased in ITP patients (Zhou et al , ), CD72 dysregulation on CD27 + memory cells was strongly correlated with anti‐platelet antibodies and platelet count. These observations suggested that the increased expression of CD72 on the CD27 + memory B subset is associated with ITP disease activity and autoantibody production.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…CD27 − B cells showed normal or slightly increased expression of CD72. Despite the fact that CD100 expression was reported not to be increased in ITP patients (Zhou et al , ), CD72 dysregulation on CD27 + memory cells was strongly correlated with anti‐platelet antibodies and platelet count. These observations suggested that the increased expression of CD72 on the CD27 + memory B subset is associated with ITP disease activity and autoantibody production.…”
Section: Discussionmentioning
confidence: 91%
“…Membrane molecules, such as CD22, CD72, the Fcc receptor (FcyR)IIb and PD-1 (also termed PDCD1) negatively regulate B cell receptor (BCR) signalling and prevent overstimulation of the B cells, whereas BCR signalling is up-regulated by membrane molecules such as CD19 (Dal Porto et al, 2004;Tsubata, 2012). Recent studies demonstrated that several of these coreceptors, including CD72, FccRIIb and CD5 have been directly linked to ITP (Iyori et al, 1995;Xu et al, 2008Xu et al, , 2010Liu et al, 2011;Zhou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that allogenic T cell responses could be inhibited through the production of immunoregulatory dendritic cells resulted by silencing RelB (Zhang et al, 2010). The expression of CD72 and IL-2 was decreased whilst the IFN-γ/IL-4 expression was increased in ITP patients (Zhou et al, 2012). Apoptotic process plays an important role in maintenance of normal immune system development, and a failure of apoptotic function has been shown to be associated with the pathogenesis of ITP (Qian et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research in recent years attempting to explicate the underlying genetic components associated with ITP, there remains much to be understood. The literature suggests a propensity towards genes associated with the activation of T cells (Anis et al , ; Chen et al , ; Li et al , ,b; Ma et al , ,b, ; Pehlivan et al , ; Rossi et al , ; Saitoh et al , ; Sarpatwari et al , ; Zhou et al , ). The observed polymorphisms included cytokines associated with the activation and survival of CD4 + T cells (Li et al , ,b; Saitoh et al , ; Sarpatwari et al , ), hypomethylation of genes associated with the proinflammatory response (Chen et al , ), CD72 gene polymorphisms and others (Anis et al , ; Pehlivan et al , ; Rossi et al , ; Zhou et al , ), all of which have been suggested to contribute to the pathophysiology of ITP.…”
Section: Genetic Studies In Immune Thrombocytopeniamentioning
confidence: 99%